Data driven estimation of foodborne disease incidence in Ethiopia - Alonso, Silvia; LaPolt, D.; Mihret, A.; Azmeraye, B.M.; Kowalcyk, B. (International Livestock Research Institute, 2022)
Objectives Surveillance of foodborne disease (FBD) remains a challenge worldwide. Available incidence estimates are based on secondary data and expert opinion and suffer from considerable uncertainty, particularly in low- and middle-income countries where the burden of unsafe foods is higher. Accurate estimates of incidence are crucial for efficient allocation of public health resources. We designed an epidemiological framework for the estimation of FBD incidence using primary data and Ethiopia as a pilot country. Materials and methods Laboratory, healthcare facility and community cross-sectional surveys were conducted simultaneously in three sites in Ethiopia. Faecal samples from diarrheal patients submitted to three clinical laboratories were tested for selected foodborne pathogens and rates of laboratory confirmed cases were estimated. Data from healthcare facilities on incidence of diarrhea among patients and referral practices; and the community on incidence of diarrhea and healthcare seeking practices were used to adjust incidence rates for under-diagnosis and under-testing. Results Between October 2021 and January 2022, 567 faecal samples were submitted; 0.8%, 13.1% and 3.7% were presumptive positive for non-typhoidal Salmonella, shiga toxin-producing Escherichia coli (STEC) and Campylobacter, respectively. Two percent (n=3,960) of individuals in the community had experienced diarrhea in the past 4 weeks, 60% of which sought healthcare, with men more likely to seek healthcare compared to women. Preliminary estimates suggest incidence of Campylobacter and STEC is significantly higher than non-typhoidal Salmonella. Pathogen-specific incidence varies greatly across regions. Conclusion Campylobacter and STEC are commonly present in diarrhea stools and their role in FBD may be larger in Ethiopia than previously believed. Results suggest that diarrhea stool screening in laboratories, currently restricted to few pathogens, is likely to provide a biased picture of the principal causes of FBD and should be expanded to include other important but currently overlooked foodborne pathogens.